(untitled) (Journal of Dhaka Medical College, 2023)
Context: Selective obturator nerve block (ONB) limits obturator reflex, adductor contraction, and leg jerking in transurethral resection of bladder tumour (TURBT), which ultimately prevents complications such as bleeding, bladder perforation, or incomplete tumor resection. The present study aims to compare the effectiveness of two different techniques of obturator nerve block during TURBT. Methods: A prospective, observational study was conducted in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, Bangladesh, between September 2018 and August 2019 to evaluate the effectiveness of ultrasound guided ONB versus cystoscopy guided ONB in TURBT operation. A total of 60 selected patients were randomly allocated into two groups: ultrasound guided ONB (group A) and cystoscopy guided ONB (group B) i.e. 30 in each group. Then onset of anesthesia (nerve block), tumour removal and patient outcome were assessed at different point during and after surgery. Results: Mean age of the patients was 54.7±8.53 years. In total, 34(57%) cases were male and 26(43%) were female. Male to female ratio was 1.3:1. In group A, 19(63.3%) patients had ASA II status and 11(36.7%) had ASA III status, while in group B, the numbers were 18(60%) and 12(40%) respectively. There was no significant difference in demographics and ASA status between two groups (P>0.05). Average onset of obturator nerve block was faster in group A (8.17±1.4 min) than group B (11.3±2.68 min), (P<0.001). Total resectability of tumours were achieved in 28(93.3%) in group A and 23(76.6%) in group B during operation (P<0.001), while 2(22.22%) and 7(77.77%) tumours had incomplete removal respectively (P<0.05). Among complications, adductor jerks were evident in 2(6.7%) and 7(23.3%), bladder perforation in 1(3.3%) and 4(13.3%), and bleeding in 1(3.3%) and 3(10.0%) cases in group A and group B respectively. The differences were statistically significant ((P<0.05). Conclusion: Although both techniques are safe and easy to perform, ultrasound guided ONB results in faster onset of block and better resectability of tumour with less complication over cystoscopy guided ONB. J Dhaka Med Coll. 2021; 30(2) : 208-213